INFLAMMATION CELL-MOLECULAR FEATURES AND SURVIVAL IN PATIENTS WITH OCCUPATIONAL CHRONIC OBSTRUCTIVE PULMONARY DISEASE FROM SILICA DUST EXPOSURE - L. I. Aftanas; L. A. Shpagina; O. S. Kotova; I. S. Shpagin; G. V. Kuznetsova; L. A. Panacheva; N. V. Kamneva; S. M. Erikhova (Сибирский научный медицинский журнал, 2019)
Objective - to establish the inflammation features and 5-years survival in occupational chronic obstructive pulmonary disease (COPD) from silica dust exposure. Material and methods. It was an observational prospective cohort study. Occupational COPD patients ( n = 101) and healthy workers ( n = 51) exposed to silica dust enrolled. Comparison group - tobacco smokers with COPD ( n = 103). Control group - healthy people without occupational health risks ( n = 99). COPD was diagnosed according to GOLD 2011-2018 criteria. Groups were matched by length of service, smoking status, demographic characteristics. Levels of inflammatory cytokines, oxidative stress markers and metalloproteinases were measured in serum by enzyme-linked immunosorbent assay. Statistical analysis - ANCOVA and multiple linear regression. Survival was analyzed using Kaplan - Meier method and Cox proportional hazard regression. Results. Occupational COPD was characterized by high serum levels of monocyte chemoattractant protein 1 (MCP1), extracellular superoxide dismutase (SOD3), fibroblast growth factor 2 (FGF2) and 8-iso-prostaglandin F2α (8-iso-PGF2α). In healthy workers exposed to silica dust an increase in FGF2, МСР1 and SOD3 was revealed. In multiple regression models length of service and dust concentrations in the workplace air were associated with molecular factors. Inflammation features were associated with lung remodeling and function. Serum level of IL1β was associated with forced expiratory volume in 1 second (В = -3.4; р = 0.028), MMP 9 content - with residual volume ratio to total lung capacity (В = 1.3; р = 0.01) and FGF2 content - with diffusing lung capacity to CO (В = -2.4; р = 0.001). The 5-year cumulative death rate from pneumonia was higher in COPD due to dust when compared with tobacco smokers COPD (5 and 2 % respectively), while there was not differences in all cause survival. Multivariate analysis revealed that length of service, dust concentrations in the workplace air, serum concentration of М??1, MMP?9, FGF2 and 8-???-PGF2? are significantly associated with mortality. СР1, MMP 9, FGF2 and 8-изо-PGF2α are significantly associated with mortality. Conclusion. Occupational COPD from silica dust exposure is a specific endotype characterized by high risk of mortality from pneumonia. In workers exposed to dust for more than 10 years FGF2 is a perspective biomarker of high occupational COPD risk.